RAPID ISOLATION OF MYCOBACTERIA-NEED OF THE HOUR IN OUR SETTINGS - Hannan, Abdul; Chaudhary, Saadia; Saleem, Sidrah; Qayyum, Atika; Arshad, Muhammad Usman (Journal of Ayub Medical College Abbottabad, 2008)
Background: To compare Bactec MGIT 960 with LJ media in terms of time taken for the initial isolation of mycobacteria. Methods: A total of 100 AFB (acid fast bacillus) positive sputum samples were processed and inoculated in both the Lowenstein Jensen (LJ) media and mycobacterium growth indicator tube (MGIT) tubes. Results: Of the 100 samples, positive growth was obtained from all the samples on both the MGIT and LJ media. In MGIT 53% samples grew in 4 days, 30% in 5 days and 17% in 6 days (Mean=4.6 days) while on LJ media, 44% grew in 30 days, 20% in 35 days and 36% in 44 days (Mean=37 days). Significant difference was observed between two systems with a p-value of less than 0.05. Conclusion: Bactec MGIT 960 is a much faster and efficient system for the initial isolation of mycobacteria. Keywords: Mycobacteria, MGIT, LJ